Perceptions of roles of community healthcare workers in early childhood in Limpopo, South Africa - Aneesa Moolla; Lezanie Coetzee; Constance Mongwenyana; Anne Robertson; Gert Marincowitz; Michele Zuckerman; Fink Günther; Davidson H. Hamer; Aisha Yousafzai; Peter C. Rockers; Denise Evans (AOSIS, 2024)
Background: As part of the Reengineering Primary Health Care initiative, the South African National Department of Health (NDoH) has committed to expanding access to home-based care provided by community health workers. The NDOH also prioritised Community Health Workers (CHWs) in their agenda to improve child development outcomes in South Africa. However, there is limited research on CHWs' experiences and knowledge of early childhood development. Aim: To explore CHWs' motivation for work, their background, training and scope of work around Early Child Development (ECD). Setting: The study was conducted in Mopani District, Limpopo province, South Africa, in 2017. Methods: Five focus group discussions (FGDs) were conducted with 41 CHWs participating within a large cluster-randomised study. Data were analysed thematically using an inductive approach. Results: Community health workers' motivation to work was influenced by personal experiences, community needs and community service. In terms of knowledge, CHWs indicated that a nutritious diet with extended breastfeeding, immunisations and preschool education is imperative for a child to thrive. The Road to Health Booklet, weighing scales and the mid-upper arm circumference tape were used as screening tools for ECD. Community health workers perceived their knowledge around ECD to be insufficient. Conclusion: Community health workers play a crucial role in healthcare; therefore, capacity development on ECD and the provision of ECD screening tools to optimise their under-five child visits are necessary. Contribution: This study will potentially contribute to the improvement of the CHW programme in ensuring that children under 5 years of age are holistically cared for to ensure that they thrive.